2014
DOI: 10.5116/ijme.5380.ca6b
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the learning and teaching of surgery: a literature review

Abstract: ObjectivesTo explore evidence concerning gender differences in teaching and learning in surgery to guide future initiatives.MethodsThis systematic review was conducted searching in the following electronic databases: MEDLINE, EMBASE, CINAHL, PsycINFO, ERIC, Web of Science, Scopus and PubMed. All studies related to gender differences in surgical education, teaching or learning of surgery at an undergraduate level were included. Data was extracted and critically appraised. Gender differences in learning, teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 60 publications
2
63
1
5
Order By: Relevance
“…In this respect, the number of women entering medical schools today exceeds 50%, and the number in hospital specialties is expected to exceed 50% by 2016 [2628]. As shown here, German numbers of the year 2013 indicate a majority of female medical students (60% of all medical students).…”
Section: Discussionmentioning
confidence: 93%
“…In this respect, the number of women entering medical schools today exceeds 50%, and the number in hospital specialties is expected to exceed 50% by 2016 [2628]. As shown here, German numbers of the year 2013 indicate a majority of female medical students (60% of all medical students).…”
Section: Discussionmentioning
confidence: 93%
“…Of note, similar results were obtained when analysis of graduating residents was performed, suggesting this perception of preparation was not dependent on postgraduate year. A survey of academic general surgeons did not find differences in confidence, decisionmaking abilities, or preparation between academic female and male surgeons [2], and previous studies in other areas of surgery have not consistently shown differences in surgical abilities between the genders [9]. A study of practicing surgeons did demonstrate that the genders rely on different strategies for developing successful careers: men relied more on training (29% versus 0% women, p < 0.05), whereas women more frequently cited social supports/networks (88% versus 12% men, p < 0.05) [10].…”
Section: Surgery Resident Preparationmentioning
confidence: 96%
“…Surgery is popular among medical students, but their enthusiasm diminishes significantly for both sexes, particularly for women, by the time they need to decide on a specialty. Reasons include the heavy workload and a desire to have children 12 . Once they become surgeons, women are more positive about their career choice than female medical students contemplating such a career 13 .…”
Section: Surgerymentioning
confidence: 99%
“…A 2014 literature review on gender‐based differences in surgical training found that the lack of role models and gender awareness were responsible for the low numbers of women training in surgery. Women were unlikely to meet a female surgical role model during their training, and were more likely to experience gender‐based discrimination during their surgical rotation ( P < 0.05), leaving them with a perception that surgery was incompatible with a rewarding family life, happy marriage, or having children 12 …”
Section: Surgerymentioning
confidence: 99%